Gut microbiota in ischemic stroke: Where we stand and challenges ahead - Long, Jiaxin; Wang, Jinlong; Li, Yang; Chen, Shuai (Frontiers in Nutrition, 2022)
Gut microbiota is increasingly recognized to affect host health and disease, including ischemic stroke (IS). Here, we systematically review the current understanding linking gut microbiota as well as the associated metabolites to the pathogenesis of IS (e.g., oxidative stress, neuroinflammation, and apoptosis). Of relevance, we highlight that the implications of gut microbiota-dependent intervention could be harnessed in orchestrating IS.